Kristologi Michael Amaladoss dalam Terang Model Antropologis Stevan B. Bevans - Alb Irawan Dwiatmaja (P3TK, Sanata Dharma University, 2021)
Jesus Christ remains the same yesterday, today and forever but changed humans can not help but think of Him differently (cf. Heb 13:8). The appreciation of the Christian faith in Jesus Christ continues to change in line with the context in which Christianity is located. Change requires everyone, both the Church, theologians, and even the people to conceptualize and discuss Jesus Christ in a new way so that Jesus Christ can be preached to different people. Michael Amaladoss contribute ideas on how Jesus Christ can be understood by people according to the context in which they live. He explain who Jesus Christ is using different methodological approaches. Amaladoss describe Jesus using images found in Asia. Through images, Amaladoss wants to show the inclusiveness of Jesus who is present for all people in all aspects of Asian life. Amaladoss reflects that Jesus, which fits the Asian context, must have a dialogue with Asian realities, namely poverty, cultural plurality, and religious plurality.